Building the next generation resurrecting the hammer throw in the USA - Bingisser, M. (New Studies in Athletics, 2013)
After dominating the hammer throw in the first six editions of the Olympic Games, the USA experienced a decline both in terms of international results and domestic participation. Medals at the top level became relatively scarce (one gold, one silver and four bronzes at the Olympics over more than 90 years) and the event all but disappeared from school and youth competitions. However, since the 1990s grass roots participation has been revived due to a number of factors and actions, including the personal efforts of the 1956 Olympic Champion Harold Connolly. The growth in the number of youth hammer throwers has been at least 400% in the last twenty years and the number of elite performers over 65m has increased at least fivefold. At the junior level, this has translated into international success (three medals, including two golds at the 2008 and 2010 IAAF World Junior Championships). The author, an active hammer thrower himself, draws on statistical analysis and survey results to chart the progress and explain the processes at work in this development. He then provides five practical recommendations on how federations or other organisations in other countries can increase participation in the hammer throw and other similarly affected events.